How Effective is Talkpal.ai in Enhancing English Proficiency? Insights from an Experimental Study - Vigo Dikaprio; Chuzaimah Dahlan Diem (Language, Technology, and Social Media, 2024)
Mastering English speaking skills is an essential competency for students of the English Education Study Program, particularly in facing the challenges of globalization. With the advancement of technology, Artificial Intelligence (AI) has emerged as a promising innovation to enhance the quality of language learning. This study aims to evaluate the effectiveness of Talkpal.ai, an AI-based application, in improving English speaking skills among second-semester students of the English Education Study Program. The research employs an experimental method with a pre-test and post-test control group design, involving 100 students randomly divided into two groups: an experimental group (n=50) using Talkpal.ai for 8 weeks, and a control group (n=50) learning through traditional teaching methods. Th e instrument used was a validated English speaking skills test, with data analysis conducted using a t-test. The results show a significant improvement in speaking skills among students in the experimental group (M=85, SD=5) compared to the control group (M=78, SD=7), with a t-value of t (98) = 5.47, p < 0.01. These findings indicate that Talkpal.ai is effective in providing a personalized and interactive learning experience, contributing to the enhancement of speaking skills. This study highlights the significant potential of AI technology in higher education, particularly in language learning, and offers recommendations for further implementation and future research.